Case Report: Parasomnia Overlap Disorder Induced by Obstructive Sleep Hypopnea Apnea Syndrome: A Case Report and Literature Review - Sun, Yun; Li, Jie; Zhang, Xinjun; Jiao, Qingyan; Yang, Shutong; Ji, Lijie (Frontiers in Neuroscience, 2020)
Obstructive sleep apnea-hypopnea syndrome (OSAHS) and parasomnia overlap disorder (POD) are types of sleep disorders. When the symptoms of both conditions coexist, the POD symptoms are most likely caused by OSAHS. In these cases, the symptoms of POD will be relieved when OSAHS is effectively treated. We refer to these cases as symptomatic POD (related to OSAHS), which differs in pathophysiology, complications, and treatment from idiopathic POD. It is important to note that the treatment for idiopathic POD may aggravate the symptoms of OSAHS. In this case, we used video polysomnography on a POD patient with suspected OSAHS to distinguish idiopathic POD from symptomatic POD, to inform the appropriate treatment course. The video results and clinical features lead us to diagnose symptomatic POD and we treated the patient with auto set-continuous positive airway pressure to address their OSAHS. This course of treatment resolved all POD related symptoms. Here we discuss this case and review the relevant literature. This report highlights the importance of the use of video polysomnography(v-PSG) in the clinical diagnosis, differential diagnosis, and subsequent treatment of POD.